Advances in the study of biological agents in the treatment of Crohn’s disease - Han-Han ZHENG; Xue-Liang JIANG (Yixue xinzhi zazhi)
Crohn’s disease (CD) is a chronic, non-specific intestinal inflammatory disease. A large number of clinical trials have shown that biological agents are effective in inducing remission in patients with CD, and mainte-nance treatment can achieve long-term remission. At present, biological agents are now being widely used in the treatment of CD and have become the main treatment. These include the anti-tumor necrosis factor (TNF)-α monoclo-nal antibodies, anti-integrin antibody, IL-12/23 monoclonal antibody and a Janus kinase (JAK) inhibitor. In this article, we review the progress and selection of biologics in the treatment of CD.